Intra-abdominal Testicular Seminoma in a Middle Aged Male: A Case Report - Alam, Md Jahangir; Mohammad, Din; Ahmed, Farhad Uddin; Ara, Rumi Farhad; Alam, Md Mahe (Journal of Science Foundation, 2018)
Cryptorchidism is a common risk factor for the testicular germ cell tumors (TGCTs). The risk of malignancy in an undescended testis is 10% with the highest risk in an intra-abdominal testis. It usually presents with non-specific symptoms so a complete systemic physical examination should not be neglected in an elderly patient with intra-abdominal mass. We here present a case of an intra-abdominal testicular seminoma in middle aged man as an asymptomatic abdominal mass. Journal of Science Foundation, January 2017;15(1):26-28